2022
DOI: 10.28927/sr.2022.076621
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on heat transfer performance of geothermal piles in a Brazilian sandy soil

Abstract: The worldwide consumption of electric energy destined for air conditioners, expected to triple by 2050, can be lessened by geothermal piles, which transfer heat from the internal environment of buildings to the subsoil. This paper shows the influence of pile geometry and properties of soil, pile, and pipe materials on the heat transfer of a geothermal pile to the surrounding soil, to support design from the viewpoint of thermal performance optimization. A numerical model was developed with ANSYS CFX 19.2, a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Systems for heating, ventilation and air conditioning consume a huge portion of the overall energy used in building services. For instance, a survey by the International Energy Agency found that, in 2016, refrigeration systems accounted for 6% of all energy supplied to buildings [2]. In the last few decades, the energy demand for cooling systems has considerably increased due to population growth, technological advancements and materialistic living standards.…”
Section: Introductionmentioning
confidence: 99%
“…Systems for heating, ventilation and air conditioning consume a huge portion of the overall energy used in building services. For instance, a survey by the International Energy Agency found that, in 2016, refrigeration systems accounted for 6% of all energy supplied to buildings [2]. In the last few decades, the energy demand for cooling systems has considerably increased due to population growth, technological advancements and materialistic living standards.…”
Section: Introductionmentioning
confidence: 99%